Novel Y-Chromosome Long Non-Coding RNAs Expressed in Human Male CNS During Early Development - Johansson, Martin M.; Pottmeier, Philipp; Suciu, Pascalina; Ahmad, Tauseef; Zaghlool, Ammar; Halvardson, Jonatan; Darj, Elisabeth; Feuk, Lars; Peuckert, Christiane; Jazin, Elena (Frontiers in Genetics, 2019)
Global microarray gene expression analyses previously demonstrated differences in female and male embryos during neurodevelopment. In particular, before sexual maturation of the gonads, the differences seem to concentrate on the expression of genes encoded on the X and Y chromosomes. To investigate genome-wide differences in expression during this early developmental window, we combined high resolution RNA sequencing with qPCR to analyse brain samples from human embryos during the first trimester of development. Our analysis was tailored for maximum sensitivity to discover Y-chromosome gene expression, but at the same time it was underpowered to detect X-inactivation escapees. Using this approach, we found that 5 out of 13 expressed gametolog pairs showed unbalanced gene dosage and as a consequence, a male biased expression. In addition, we found 6 novel non-annotated long non-coding RNAs on the Y-chromosome with conserved expression patterns in newborn chimpanzee. The tissue specific and time restricted expression of these long non-coding RNAs strongly suggests important functions during central nervous system development in human males.